Developing leadership within 4-H and UW-Extension youth programs survey report - Trechter, David; Hadley, Shelly (My University, 2010)
The purposes of this statewide survey were to describe the scope of and participation in 4-H and UW-Extension youth development leadership programming for youth in 7th-13th grades and to measure the impact of these programs on participants in terms of their leadership skills, confidence, and behaviors.
46 p.
Keywords: UW-Extension; 4-H clubs; 4-H clubs--Wisconsin; Leadership; Youth development leadership program; 4-H